Soft Red Winter Wheat Elite Germplasm Screening and Evaluation for Stripe Rust in the US Southeast Region - Ehsan Shakiba; Noah DeWitt; Ali Babar; Richard E. Boyles; Mohamed Mergoum; Russell Sutton; Jeanette Lyerly; Paul Murphy; Stephen Harrison (Agriculture, 2024)
Stripe rust is a severe disease affecting wheat (Triticum aestivum L.) production in the United States Southeast region, necessitating the identification of resistant sources. The study was conducted at the University of Arkansas, Fayetteville, and utilized a Randomized Block Design over three years. A total of 1130 lines were inoculated annually, and their responses for stripe rust were recorded. The results revealed that 11%, 79%, and 77% of the lines showed resistance in the first, second, and third years, respectively, with an overall 50% of the whole population. Linear Mixed Model and Generalized Estimating Equation analyses highlighted environmental influences, with cooler, humid conditions in 2021 favoring stripe rust, while warmer, variable conditions in 2022 and stable weather in 2023 contributed to lower disease severity. Data analysis of infection rates and disease development indicated that the newer generations of wheat lines tested in 2022 and 2023 exhibited higher resistance lines, lower infection rates, and slower disease progression. The findings support targeted breeding strategies for durable stripe rust resistance, emphasizing the importance of multi-environment testing and selection of lines with adult-plant resistance traits. This research offers valuable insights for breeders, agronomists, and farmers aiming to mitigate stripe rust impact through improved cultivars and informed management practices.